Lipopolysaccharide Stimulates Butyric Acid-Induced Apoptosis in Human Peripheral Blood Mononuclear Cells - Kurita-Ochiai, Tomoko (American Society for Microbiology, 1999)
We previously reported that butyric acid, an extracellular metabolite from periodontopathic bacteria, induced apoptosis in murine thymocytes, splenic T cells, and human Jurkat T cells. In this study, we examined the ability of butyric acid to induce apoptosis in peripheral blood mononuclear cells (PBMC) and the effect of bacterial lipopolysaccharide (LPS) on this apoptosis. Butyric acid significantly inhibited the anti-CD3 monoclonal antibody- and concanavalin A-induced proliferative responses in a dose-dependent fashion. This inhibition of PBMC growth by butyric acid depended on apoptosis in vitro. It was characterized by internucleosomal DNA digestion and revealed by gel electrophoresis followed by a colorimetric DNA fragmentation assay to occur in a concentration-dependent fashion. Butyric acid-induced PBMC apoptosis was accompanied by caspase-3 protease activity but not by caspase-1 protease activity. LPS potentiated butyric acid-induced PBMC apoptosis in a dose-dependent manner. Flow-cytometric analysis revealed that LPS increased the proportion of sub-G(1) cells and the number of late-stage apoptotic cells induced by butyric acid. Annexin V binding experiments with fractionated subpopulations of PBMC in flow cytometory revealed that LPS accelerated the butyric acid-induced CD3(+)-T-cell apoptosis followed by similar levels of both CD4(+)- and CD8(+)-T-cell apoptosis. The addition of LPS to PBMC cultures did not cause DNA fragmentation, suggesting that LPS was unable to induce PBMC apoptosis directly. These data suggest that LPS, in combination with butyric acid, potentiates CD3(+) PBMC T-cell apoptosis and plays a role in the apoptotic depletion of CD4(+) and CD8(+) cells.